2021
DOI: 10.5194/egusphere-egu21-10252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ microplastics ingestion by Antarctic marine benthic invertebrates

Abstract: <p>Microplastics have been recognised as persistent marine contaminants and mounting evidence supports their designation as anthropogenic stressors to marine organisms. Despite the remoteness of Antarctica, microplastics contamination has been reported in every marine environment investigated in this area to date. Due to ocean currents and frontal systems, microplastics may become entrapped within polar regions and increase bioavailibilty to inhabiting fauna. Antarctic marine benthic invertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In contrast to zooplankton, the types in benthic organisms were nitrile and EVA. Hoellein et al (2017) and Hurley et al (2021) reported that nitrile and EVA polymer types were commonly abundant in benthic organisms. This study also revealed that the dominant polymer type of MPs in fish was nitrile and EVA (Figure 7(a)).…”
Section: Mps In Aquatic Faunamentioning
confidence: 99%
“…In contrast to zooplankton, the types in benthic organisms were nitrile and EVA. Hoellein et al (2017) and Hurley et al (2021) reported that nitrile and EVA polymer types were commonly abundant in benthic organisms. This study also revealed that the dominant polymer type of MPs in fish was nitrile and EVA (Figure 7(a)).…”
Section: Mps In Aquatic Faunamentioning
confidence: 99%
“…Microplastics are ubiquitous, from high-altitude inland lakes (Zhang et al, 2016;Çomaklı et al, 2020;Pastorino et al, 2021) to remote areas such as deep-sea environments (Zhu et al, 2019;Barrett et al, 2020;Zhang et al, 2020), islands (Imhof et al, 2017;Nel et al, 2020;Tan et al, 2020), the Arctic and the subarctic regions (Obbard et al, 2014;Cózar et al, 2017;Fang et al, 2018;Hurley et al, 2021). Studying the MPs dynamic is essential to better understand the distribution and bioavailability in the water column (Galloway et al, 2017;Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%